Разработка и исследование характеристик плазменно-топливных форсунок - Сербин, С. И.; Кирчук, Е. Ю. (НТУ "ХПИ", 2010)
A number of plasma-fuel nozzle constructions are developed and tested volt-ampere characteristics and fuel atomization quality are determined. Parameters of the universal plasma-fuel nozzle working on various gaseous and liquid fuels in a wide range of air flow rate and fuel consumptions are defined.
Keywords: использование энергоресурсов; углеводородные топлива; камеры сгорания; топочные устройства